Beyond the extreme: recovery of carbon and water relations in woody plants following heat and drought stress. (17th May 2019) - Ruehr, Nadine K; Grote, Rüdiger; Mayr, Stefan; Arneth, Almut
Abstract: Plant responses to drought and heat stress have been extensively studied, whereas post-stress recovery, which is fundamental to understanding stress resilience, has received much less attention. Here, we present a conceptual stress-recovery framework with respect to hydraulic and metabolic functioning in woody plants. We further synthesize results from controlled experimental studies following heat or drought events and highlight underlying mechanisms that drive post-stress recovery. We find that the pace of recovery differs among physiological processes. Leaf water potential and abscisic acid concentration typically recover within few days upon rewetting, while leaf gas exchange-related variables lag behind. Under increased drought severity as indicated by a loss in xylem hydraulic conductance, the time for stomatal conductance recovery increases markedly. Following heat stress release, a similar delay in leaf gas exchange recovery has been observed, but the reasons are most likely a slow reversal of photosynthetic impairment and other temperature-related leaf damages, which typically manifest at temperatures above 40 °C. Based thereon, we suggest that recovery of gas exchange is fast following mild stress, while recovery is slow and reliant on the efficiency of repair and regrowth when stress results in functional impairment and damage to critical plant processes. We further propose that increasing stress severity, particular after critical stress levels have been reached, increases the carbon cost involved in reestablishing functionality. This concept can guide future experimental research and provides a base for modeling post-stress recovery of carbon and water relations in trees.